Mathematical models of digital transformation asymmetric information game in energy enterprises - Caicai Guo; Riqiang Li; Bei Yuan (Alexandria Engineering Journal)
Energy enterprises play a crucial role in the development of the national economy and heavily rely on government financial subsidies. With the advent of the digital economy era, the digital transformation of energy enterprises has become an imperative requirement for green development. The digital economy will influence the decision-making of energy companies by improving their efficiency and reducing their costs. However, due to the presence of information asymmetry, the decision-making of energy enterprise management deviates from government expectations. This paper constructs an asymmetric information game model from a game theory viewpoint, studying the incentive and constraint mechanism by which government subsidies promote the digital transformation of energy enterprises. Taking multiple games as a breakthrough, this paper studies the whole decision-making process from ex-ante assumptions to ex-post analysis through the perspectives of government-enterprise game, subsidy effect, capital market and debt market. The results shown that government subsidies which supporting digital transformation can encourage enterprises to lower their digital transformation investment, thereby enhancing the market value. In addition, government subsidies can cause a reaction in the stock prices of energy companies, and act as a signaling mechanism for the financial sector to discern creditworthiness among energy companies.